OPTIMIZATION OF CONSTRUCTIVE AND TECHNOLOGICAL PARAMETERS OF ROTARY SOIL TILLER - Замойський, С. М.; Замойська, К. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The park of agricultural tillage machines in most households is rundown and insufficient for cultivation during crops sowing in optimal agronomic terms. Soil processing surface for crops sowing is tilled with the help of cultivating instruments based on active and passive tools. Better quality of the soil provide active tools, but they have some disadvantages. The main disadvantage is the lack of heeling stubble and stubble deads in the soil. Moreover, cultivating instruments have complex structure, low technological reliability of machines and high metal content. Such characteristics reduce the efficiency of the processe. The production of agricultural machinery in the agricultural sector of Ukraine is increasing. First of all, it is the production of preplant tillage cultivation equipment. Agricultural machinery enterprises started to suggest cultivating tools with the active working tools instead of traditional instruments with passive working tools. The construction of equipment combines several methods of grinding ground that provide a high quality structure and size of the structural units. The methods of theoretical studies determining structural and technological parameters of rotary ripper soil and their impact on soil processing surface for crops planting are used in the study.